Efficacy of Old and New Generation Antibiotics in MDR Staphylococcus Aureus Isolated From UTI - Weam Saad Al-Hamadany (Journal of Global Pharma Technology, 2019)
The medical problem of acquired antibiotic resistance for clinical Staphylococcus aureus is a global concern. Scientist's efforts are to focus light on the alternative antibiotics for treatment of the isolates that exhibited resistance against classical antibiotics. Recurrent UTI is the commonest nosocomial infection caused by MDR S. aureus and the antibiotic treatment becomes an important issue. Methods and Materials: a total of (14) S. aureus isolates were tested in vivo for antibiotic resistance using disc diffusion method, antibiotics used were Methicillin (Me), Cefamandole (MA), Carbencillin (Py), Vancomycin (Van) and Lomofloxacin (Lom). Results: showed that both of the antibiotics Van and Lom had the highest records of sensitive isolates 13 (92.8%), while the antibiotic me recorded the highest number of resistant isolates 8 (57.2%) from the total 14 isolates. Both MA and Py recorded 9 (64.3%) as sensitive isolates. Conclusion: Antibiotics resistance exhibited by S. aureus is an obvious problem mainly for critical cases that need an urgent management with no time to loss, antibiotic sensitivity test should be an obligatory procedure before giving antibiotics to avoid acquired resistance. Old generation antibiotics Methicillin, Cefamandole and Carbencillin need to be tested for efficacy on S. aureus isolates before use on, new generation antibiotics Vancomycin and Lomofloxacin are very effective in treatment of vigorous S. aureus clinical isolates of recurrent UTI.Keywords: Multidrug resistance, Staphylococcus aureus, Antibiotic, Antibiotic sensitivity test and recurrent UTI.